Topics in Climate Modeling - Hromadka, Theodore; Rao, Prasada (IntechOpen, 2016)
The topics of climate change, weather prediction, atmospheric sciences and other related fields are gaining increased attention due to the possible impacts of changes in climate and weather upon the planet. Concurrently, the increasing ability to computationally model the governing partial differential equations that describe these various topics of climate has gained a great deal of attention as well. In the current book, several aspects of these topics are examined to provide another stepping stone in recent advances in the fields of study and also focal points of endeavor in the evolving technology.